Breakthrough : from pandemic panic to promising practice - McCarther, Shirley Marie; Davis, Donna M. (History of education book series., 2023)
"The Organization of Educational Historians Book Series, published by Information Age Publishing, presents historical analyses and interpretations of matters of concern to education. Each volume in the series is developed and edited in partnership with the Organization of Educational Historians, who, since 1965, has endeavored to promote the pursuit of educational history through opportunities for presentation and discussion of papers at annual meetings, to advance and improve the teaching of the history of education in institutions of higher education, to cultivate fruitful relationships between scholars in the history of education, and to encourage promising young scholars in the field of history of education"--